Regional VRE surveillance using routine centralised, multicentre whole genome sequencing - Djamayl L. H. H. Engelen; Jean-Luc Murk; Veronica A. T. C. Weterings; Heike Schmitt; Bram M. W. Diederen; Andreas L. E. van Arkel; Jaco J. Verweij; Wouter van den Bijllaardt; Jeroen H. T. Tjhie; Joep J. J. M. Stohr (PLoS ONE, 2026)
Objective Whole genome sequencing (WGS) is increasingly used to support infection prevention and control. However, its application for routine regional surveillance of vancomycin-resistant Enterococcus faecium (VREfm) across multiple healthcare facilities is still evolving. This study describes the implementation of routine centralised multicenter WGS surveillance of VREfm and explores its utility for detecting clusters and investigating transmission within and between healthcare institutions in a regional healthcare network. Methods VREfm isolates identified from patient samples (clinical and screening) in five different hospitals in the Netherlands during a one-year period were whole genome sequenced and typed using core genome multilocus sequence typing (cgMLST). Sequence data were correlated with admission data of the year prior to the first positive VREfm culture of the respective patients. By combining epidemiological and sequence data within and between hospital transmission events were identified. Results 57 VREfm isolates were detected during the study period. 38/57 (66.7%) isolates clustered with at least one other isolate. Based on our definitions, intrahospital transmission could be demonstrated in 37 of 38 cases and interhospital transmission in 3 of 38 cases. Using this approach, a multicenter outbreak and two local outbreaks were detected. Conclusions Routine whole genome sequencing of VREfm is a powerful tool for detecting, tracing and delineating outbreaks. When integrated into a centralised surveillance system spanning collaborative healthcare networks, it becomes an essential tool for unraveling the complex transmission dynamics of VRE within and between hospitals, ultimately strengthening infection control strategies.